2016
DOI: 10.1002/2015jc011225
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the directional distribution of the wind energy input function over swell waves

Abstract: Field measurements of wind stress over shallow water swell traveling in different directions relative to the wind are presented. The directional distribution of the measured stresses is used to confirm the previously proposed but unverified directional distribution of the wind energy input function. The observed wind energy input function is found to follow a much narrower distribution ( β∝cos⁡3.6θ) than the Plant (1982) cosine distribution. The observation of negative stress angles at large wind‐wave angles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Based on the eddy covariance method, which has been widely utilized (Aubinet et al, ), the wind stress at a given height above the surface can be represented by the following: bold-italicτ=τx+τy=ρa⟨⟩uwbold-italiciρa⟨⟩vwbold-italicj Here τ x is the longitudinal or downwind stress; τ y is the lateral or crosswind stress; 〈 〉 is a time or spatial averaging operator that represents the Reynolds average; and u ′ , v ′ , and w ′ are the longitudinal, lateral, and vertical velocity fluctuations, respectively (Grachev et al, ). Moreover, τ x and τ y can be represented by τ x = ρ a C Dx U 2 and τ y = ρ a C Dy U 2 , respectively, referring to the coordinate framework of Shabani et al (). Here ρ a is the air density, U is the wind speed, and C Dx and C Dy are the downwind and crosswind drag coefficient, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the eddy covariance method, which has been widely utilized (Aubinet et al, ), the wind stress at a given height above the surface can be represented by the following: bold-italicτ=τx+τy=ρa⟨⟩uwbold-italiciρa⟨⟩vwbold-italicj Here τ x is the longitudinal or downwind stress; τ y is the lateral or crosswind stress; 〈 〉 is a time or spatial averaging operator that represents the Reynolds average; and u ′ , v ′ , and w ′ are the longitudinal, lateral, and vertical velocity fluctuations, respectively (Grachev et al, ). Moreover, τ x and τ y can be represented by τ x = ρ a C Dx U 2 and τ y = ρ a C Dy U 2 , respectively, referring to the coordinate framework of Shabani et al (). Here ρ a is the air density, U is the wind speed, and C Dx and C Dy are the downwind and crosswind drag coefficient, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…, v 0 , and w 0 are the longitudinal, lateral, and vertical velocity fluctuations, respectively (Grachev et al, 2003). Moreover, τ x and τ y can be represented by τ x = ρ a C Dx U 2 and τ y = ρ a C Dy U 2 , respectively, referring to the coordinate framework of Shabani et al (2016). Here ρ a is the air density, U is the wind speed, and C Dx and C Dy are the downwind and crosswind drag coefficient, respectively.…”
mentioning
confidence: 99%
“…Continuous measurements for four weeks in May-June 2016 were divided into 15-min blocks for analysis. The analysis for computing momentum fluxes and procedures for quality controlling the data is given in Aubinet et al (2012), which is similar to that described by Shabani et al (2014) and Ortiz-Suslow et al (2015).…”
Section: Field Experimentsmentioning
confidence: 99%
“…Anctil and Donelan (1996) found increased C d values for waves shoaling from 12 m to breaking in 2-m water depth. Shabani et al (2014Shabani et al ( , 2016 found that measured C d for near-neutral, atmospheric stability over the shoaling region and surfzone were O(2) times larger than open-ocean estimates, which they ascribe to the wave celerity c and shape effects. Similar to Anctil and Donelan (1996), they suggested that as the wave shoals, wave speed slows relative to the wind speed U increasing C d .…”
Section: Introductionmentioning
confidence: 99%
“…These provided 3D turbulent velocity measurement, which digital signal was fed into the data logger and logged synchronously with other instruments. This was the same wind measurement and logging equipment as was used by Shabani et al (2014) and Shabani et al (2016), although deployed at a different location, using a different support structure and positioned at different elevations.…”
Section: Wind Measurementmentioning
confidence: 99%